2022
DOI: 10.1093/jnci/djac011
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Glycemic Traits and Colorectal Cancer: A Mendelian Randomization Analysis

Abstract: Background Glycemic traits—such as hyperinsulinemia, hyperglycemia, and type-2 diabetes—have been associated with higher colorectal cancer risk in observational studies; however, causality of these associations is uncertain. We used Mendelian randomization (MR) to estimate the causal effects of fasting insulin, 2-hour glucose, fasting glucose, glycated hemoglobin (HbA1c), and type-2 diabetes with colorectal cancer. Methods Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 44 publications
(46 reference statements)
1
41
0
Order By: Relevance
“…Third, evening chronotype has been associated with DNA methylation of certain gene sites, like BACH2 , JRK and RPS6KA2 , which are related to the cancer development 39 . Fourth, evening chronotype may be associated with impaired metabolic homeostasis, like insulin resistance and increased levels of low‐density lipoprotein, 40 which have been associated with an increased risk of colorectal cancer 41,42 . In addition, increased levels of BMI have been proposed to be a possible mediator in the association between chronotype and digestive tract cancer since people with morning preference have a decreased frequency of obesity 43 that is a causal risk factor for digestive tract cancers 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Third, evening chronotype has been associated with DNA methylation of certain gene sites, like BACH2 , JRK and RPS6KA2 , which are related to the cancer development 39 . Fourth, evening chronotype may be associated with impaired metabolic homeostasis, like insulin resistance and increased levels of low‐density lipoprotein, 40 which have been associated with an increased risk of colorectal cancer 41,42 . In addition, increased levels of BMI have been proposed to be a possible mediator in the association between chronotype and digestive tract cancer since people with morning preference have a decreased frequency of obesity 43 that is a causal risk factor for digestive tract cancers 5 .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 35 studies involving 25,566 cases showed that higher FI levels were significantly associated with an increased risk of colorectal cancer ( 37 ). A recent MR study also validated the association between FI and colorectal cancer risk ( 38 ). In contrast, a longitudinal study with a median follow-up period of 11.9 years demonstrated that serum insulin was not related to the risk of colorectal cancer in postmenopausal women ( 39 ).…”
Section: Discussionmentioning
confidence: 83%
“…The results of this previous study are comparable to those of the present study. Further, a mendelian randomization analysis by Murphy et al showed that fasting glucose exerted no effect on the risk of developing CRC ( 27 ). To date, this is the largest and most comprehensive study examining the effects of multiple glycemic profiles on CRC risk ( 27 ).…”
Section: Discussionmentioning
confidence: 99%